Relationship between child temperament and maternal parenting behaviour amongst preschool children in Serdang, Selangor, Malaysia - Indran, Rohini (2016)
The main objective of this study was to examine child emotional and behaviour problems of externalising and internalising behaviours and its relationship with child temperament and maternal parenting behaviours amongst preschool children in Serdang, Selangor. Teachers of 387 children aged 4 to 6 years old from identified preschools filled the Caregiver Teacher Report Form (CTRF) to screen children with emotional and behaviour problems. Subsequently, a further questionnaire was distributed to mothers of the children to examine child temperament via the Child Behaviour Questionnaire (CBQ) and maternal parenting behaviours via the Parental Acceptance-Rejection Questionnaire (PARQ). The results found that child temperament of negative affectivity predicted both externalising and internalising behaviour problems. Moreover, the results analysed also concluded that lack of maternal warmth and acceptance and a prevalence of maternal rejection most significantly contributed to the development of externalising and internalising behaviour problems in the respondents. Furthermore, the study found that the relationship between effortful control and surgency and externalising behaviour problems were fully mediated by maternal parenting behaviour while negative affectivity and externalising and internalising behaviours were partially mediated by maternal parenting behaviours. Thus, negative maternal parenting behaviour has been identified as the strongest predictor of behaviour problems in preschool children validating the importance of mother-child relationships via proximal processes. This stresses the importance of intervention programs to strengthen motherchild relationships while screening and early warning mechanisms should be implemented to prevent the issue from being overlooked. Additionally, based on the National Child Protection policy, it is recommended to increase awareness and efforts to protect a child, encourage safe and healthy environments for children and increase support services for positive child development.